21 Adenosine-producing B cells in patients with head and neck cancer. Issue 5 (May 2015) - Huber, U.; Ziebart, A.; Schwarz, S.; Jerg, M.; Laban, S.; Hoffmann, T.K.; Schuler, P.
<x xml:space="preserve">Abstract</x> Purpose Head and Neck Squamous Cell Carcinoma (HNSCC) induces profound immune defects, which are associated with increased metastasis and recurrent disease. Recently, we demonstrated that regulatory B cells (Breg) play a significant role in the production of extracellular adenosine (ADO), which is known to be highly immunosuppressive. To this end, exogenous ATP is hydrolyzed to ADO by ectonucleotidases, CD39 and CD73. Here, we examined the influence of cancer disease and cancer treatment on the Breg population. Experimental design Peripheral blood mononuclear cells (PBMC) were obtained from healthy donors, patients with active HNSCC, and patients after treatment. The number, frequency and phenotype of Breg was determined by multicolor flow cytometry. Next, B cells were isolated from healthy donors by CD19+ magnetic beads, stimulated (CD40L, IL-4, hemagglutinin) and incubated with physiologic concentrations of chemokines (TGF-ß, IL-10) or various chemotherapeutic drugs (cisplatin, methotrexate, paclitaxel, 5-fluorouracil, cetuximab) for 7 days. Effects on Breg proliferation were determined by CFSE proliferation assay. Production of extracellular ADO was determined by ATP luminescence assay as well as highly sensitive mass spectrometry measuring 5'AMP, ADO and inosine. Long-term effects were described analyzing Breg from patients who had received chemotherapy several years ago. Results Breg were numerically diminished in untreated HNSCC patients. However, after chemotherapy the frequency of B cells was increased due to a strong decrease of CD4+ T cells. Incubation with TGF-ß and IL-10 induced proliferation and expression of ectonucleotidases on Breg. Chemotherapeutic drugs had variable effects in vitro: While cisplatin, paclitaxel and 5-fluorouracil decreased the expression of CD39, it increased under methotrexate. Importantly, hydrolysis of ATP to exogenous ADO correlated strongly with CD39 expression levels (R2 = 0.6). CD73 expression levels were increased by all drugs, except for cetuximab, which showed no effect on phenotype or function. Conclusion Highly suppressive Breg increase in frequency after chemotherapy and could be responsible for suppression of antitumor immune responses and recurrent disease in HNSCC. B cell function in terms of ADO production is compromised by various chemotherapeutic drugs amplifying therapeutic benefits.